1984
DOI: 10.1002/j.1556-6978.1984.tb00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cross‐Cultural Training on Helper Response

Abstract: This study investigated the effects of cross-cultural training on participants' empathic response, attending behavior, and anxiety during interviews with a culturally dissimilar Black client. Thirty-one White graduate trainees in counseling were randomly assigned to treatmentho-treatment conditions; the treatment group was exposed to cross-cultural training. Trained judges rated videotaped excerpts of trainee performance on empathy and attending behavior variables; a self-report measure of anxiety was used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The most prominent features of our density model appear near the CMB, where high-density anomalies are found in regions of mantle uplift beneath the Pacific and Africa. This observation is consistent with convection sirnulations where dense material piles up beneath upwellings because it is too heavy to be entrained in the uplift (36). Introduction of heavy core material into the mantle beneath upwellings can also cause such density anomalies (37).…”
Section: Robustness Of the Modelssupporting
confidence: 77%
“…The most prominent features of our density model appear near the CMB, where high-density anomalies are found in regions of mantle uplift beneath the Pacific and Africa. This observation is consistent with convection sirnulations where dense material piles up beneath upwellings because it is too heavy to be entrained in the uplift (36). Introduction of heavy core material into the mantle beneath upwellings can also cause such density anomalies (37).…”
Section: Robustness Of the Modelssupporting
confidence: 77%
“…Christensen (1984) found that supervisees' empathic responses, attending behavior, and anxiety level during interviews with culturally dissimilar clients were not significantly different between a control group and a group receiving training on cross-cultural counseling issues. Cook and Helms (1988) reported that in cross-cultural supervision, supervisee perceptions of the supervisors' liking and positive feelings toward the supervisee were significant predictors for relationship satisfaction.…”
mentioning
confidence: 80%
“…By virtue of the trainee's identification with the profession, supervisors can mistakenly assume that trainees identity with them culturally as well" (p. 198). Bernard and Goodyear (1992) brought their ideas together in a stage model for the development of cross-cultural awareness adapted from Christensen (1984). In this model, the supervisor's job is to help supervtsees advance by providing appropriate levels of challenge and support.…”
Section: Clinical and Theoretical Literaturementioning
confidence: 99%
“…In the last 20 years, the literature on cross-cultural issues in counseling psychology has increased exponentially (Christensen, 1984;D'Andrea & Daniels, 1991;D'Andrea, Daniels, & Heck, 1991;Heath, Neimeyer, & Pedersen, 1988). General theories and models based on White middle-class male values have been challenged as inappropriate for American minorities who may not share the assumptions, norms, orworldviews of the majority, The growth of this literature, however, has been limited to certain areas within counseling such as cross-cultural counseling and assessment.…”
mentioning
confidence: 99%